2005
DOI: 10.1523/jneurosci.3284-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Dynamics Do Not Determine Proper Phase of Activity in a Central Pattern Generator

Abstract: Rhythmic motor activity often requires neuronal output to the muscles to arrive in a particular sequence. At the pattern-generator level, this requires distinct activity phases in different groups of constituent neurons. The phase differences between rhythmically active neurons in a network are thought to arise from the interplay between their intrinsic properties and the temporal dynamics of synapses among these neurons. In the rhythmically active pyloric network of the lobster Panulirus interruptus, synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 87 publications
4
36
0
Order By: Relevance
“…It also revealed a number of interesting facts about how the dynamics of the network evolve. For example, it has traditionally been thought that the primary role of the PY to LP synapse is simply to return LP to its silent state [27]. Our analysis now demonstrates that an additional effect of this synapse is to strengthen the LP to PY synapse by causing LP to spend more time in its silent state, allowing for recovery from short-term depression.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It also revealed a number of interesting facts about how the dynamics of the network evolve. For example, it has traditionally been thought that the primary role of the PY to LP synapse is simply to return LP to its silent state [27]. Our analysis now demonstrates that an additional effect of this synapse is to strengthen the LP to PY synapse by causing LP to spend more time in its silent state, allowing for recovery from short-term depression.…”
Section: Discussionmentioning
confidence: 54%
“…The functions m ∞ , w ∞ , and τ ∞ are sigmoidal functions of voltage and are given in the Appendix. Recent experiments by Rabbah et al [27] showed that the delay in firing of PY relative to firing of LP is due to intrinsic properties of the neurons. Thus, in the silent state, we choose τ w,LP (v LP ) < τ w,PY (v PY ) so that PY has a a slower intrinsic decay rate than LP.…”
Section: Modelmentioning
confidence: 99%
“…It is important to note that was is no a priori expectation for the phase lags to change with the synaptic modification (Eisen and Marder 1984;Rabbah and Nadim 2005). In our experiments, the rebound properties of the PD could keep the phase lag almost constant as the synaptic strength was changed, simply as a result of the PD rebounding faster when the inhibition is stronger, a normal feature observed in almost all neurons.…”
Section: Discussionmentioning
confidence: 63%
“…Endogenous membrane currents strongly influence PIR (Rabbah and Nadim, 2005). I A and I h decrease and increase the rate of PIR, respectively (Tierney andHarris-Warrick, 1992, 1995a).…”
Section: Dopaminergic Systems Are Organized To Prevent Disruptions Inmentioning
confidence: 99%